Attitude, knowledge and practice related to oral hygiene among urban Babolian population between 20-40 years old - M Khosravi (Babol University of Medical Sciences, 2004)
Background and Objective: The high prevalence of oral diseases and complexities existing in their treatment has been resulted in great emphasis on prevention measures. The purpose of this study was to assess the oral hygiene attitude, knowledge and practice in Babol community. Methods: This descriptive and cross-sectional study was performed on 400 people aged between 20-40 years old who chosen randomly from 10 urban clusters of Babol in 2002-2003. The questionnaires were organized in relation to attitude and knowledge, practice and than the data after scoring were analyzed. Findings: Among subjects, 181 were female and 219 were male. Mean attitude and knowledge score was 8.9±3.7 (Max Att=20). The level of attitude and knowledge score was achieved higher in educated (P=0.0001) and younger (P=0.029) people. Mean practice score was 3.5±0.6 (Max Beh=10). The level of practice score was achieved higher in educated and younger people (P=0.0001, P=0.04, respectively). Also, the level of practice was achieved higher in women (P=0.005) and finally single people had higher attitude and knowledge (P=0.014) and practice than married ones. Conclusion: With respect to unfavorite status of attitude, knowledge and practice regarding oral health, introduction of preventive dental services and establishment of community based on oral health promotion programs are urgently needed for these population.